2013
DOI: 10.1016/j.ijrobp.2013.06.2044
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Noninferiority Trial of Reduced High-Dose Volume Versus Standard Volume Radiation Therapy for Muscle-Invasive Bladder Cancer: Results of the BC2001 Trial (CRUK/01/004)

Abstract: PurposeTo test whether reducing radiation dose to uninvolved bladder while maintaining dose to the tumor would reduce side effects without impairing local control in the treatment of muscle-invasive bladder cancer.Methods and MaterialsIn this phase III multicenter trial, 219 patients were randomized to standard whole-bladder radiation therapy (sRT) or reduced high-dose volume radiation therapy (RHDVRT) that aimed to deliver full radiation dose to the tumor and 80% of maximum dose to the uninvolved bladder. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 18 publications
3
70
0
6
Order By: Relevance
“…Randomized trials have attempted to harness the dosimetric advantages of PB hypofractionation for dose escalation and have shown no excess toxicity; further exploration of the possibilities would be worthwhile. [15][16][17] Our patients had higher bladder-intact survival rates compared with induction BPCR patients than might be expected. Perhaps (as in head and neck and cervical cancers) treatment duration is relevant.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Randomized trials have attempted to harness the dosimetric advantages of PB hypofractionation for dose escalation and have shown no excess toxicity; further exploration of the possibilities would be worthwhile. [15][16][17] Our patients had higher bladder-intact survival rates compared with induction BPCR patients than might be expected. Perhaps (as in head and neck and cervical cancers) treatment duration is relevant.…”
Section: Resultsmentioning
confidence: 54%
“…28 Similar to recent reports on reduced bladder volume receiving high-dose radiation, our data showed that hypofractionated true PB only radiation trended toward improved local control and survival. 16,17 One shortcoming is that with a small number of patients, our study was underpowered to validate this finding, but the results are intriguing nonetheless. Hypofractionation should translate into an LC advantage as the accelerated repopulation and short doubling times of tumor cells would favor shorter overall treatment regimens, and image-guidance facilitates dose escalation.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…La non-infériorité n'a pu être prouvée dans l'essai de Huddard et al due à une faible puissance statistique, le bras de cet essai ayant été clôturé prématurément. Il n'en reste pas moins que ces deux essais ont donné des résultats équivalents : des taux de contrôle local et de survie comparables entre les deux bras sans différence significative de toxicité [62,63].…”
Section: Irradiation Partielle De La Vessieunclassified